Assessment of Contractor's Contribution Towards Green Waste Management - Yong, H.; Rosli, M.; Chong, Heap Yih; Balubaid, S. (Universiti Teiknologi Malaysia, 2013)
Effective waste management and its contribution in green aspects at construction site is the cutting edge sustainability research in construction industry. This paper highlights overview on waste management, types of building waste and more importantly the formulation of a conceptual framework to assess the performance of contractors’ contribution towards green waste management within Malaysian context. The discussion will also cover the exploration of the significant parameters required to be included in the scoring system emphasizing on the green issues in the construction industry. The green building index (GBI) appraisal system will be used as a guide to develop a more suitable and effective score measuring tool to assess the levels of green waste management contribute by contractors. The intentions are to promote the awareness of the green waste management and attract serious participations from contractors towards sustainable construction in the industry which in turn, helps to reduce the building material waste which is usually been ended up at the landfill or worst still dumped illegally on the unspecified areas.